Effect of S, Ca and Mg on fresh rhizome yield of turmeric (Curcuma longa L.) - Sanghamithre, V.K.; Menon, Meera V. (Journal of Tropical Agriculture, 2014)
The effect of the secondary elements, viz., sulphur, calcium and magnesium on the yield of turmeric (Curcuma longa L.) was studied at the Department of Agronomy, College of Horticulture, Vellanikkara from 2013-2014. Ten treatments were evaluated which included 25 kg ha-1 each of sulphur, calcium and magnesium applied separately and in combination at 30 and 60 days after planting along with recommended dose of manures and fertilizers for turmeric as per package of practices recommendations of the Kerala Agricultural University. The experiment was laid out in randomized block design with three replications. Application of calcium @ 25 kg ha-1, 60 days after planting and magnesium @ 25 kg ha-1 , 30 days after planting along with package of practices recommendation of Kerala Agricultural University significantly enhanced dry matter production at 6 months after planting and fresh rhizome yield. A yield increase of 33.77 percent and 29.27 percent were recorded in the above treatments over the recommended package of practices of Kerala Agricultural University. Highest yields were associated with highest calcium contents in shoots at six months after planting.